2016
DOI: 10.1016/j.jpcs.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties of Nd3+-doped tungsten–tellurite glasses

Abstract: In this work, we investigate the spectroscopy properties of neodymium doped tungsten-tellurite glasses prepared in ambient and O 2-rich atmospheres. A conversion of TeO 4 to TeO 3 units was caused by the addition of Nd 3 þ into the glass, which was confirmed by absorption spectra and by Judd-Ofelt parameter behavior. The relaxation of the 4 F 3/2 level is dominated by radiative decay and cross-relaxation between Nd 3 þ and Nd 3 þ ions. The energy transfer from Nd 3 þ to the hydroxyl group is negligible when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 38 publications
4
10
1
Order By: Relevance
“…A linear dependence was observed for the Yb 3+ absorption (at 978 nm) vs concentration of Yb 3+ ions (not shown), indicating successful incorporation of Yb 3+ into the prepared glasses. A blue shift of the absorption edge is also observed, indicating that the addition of Yb 3+ caused a change in the glass structural units from TeO 4 (tbp=trigonal bi‐pyramid) to TeO 3 (tp=trigonal pyramid) . Similar changes were reported recently for Nd 3+ added to a TW host, promoting a slight reduction in its phonon energy (~942 cm −1 ) …”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…A linear dependence was observed for the Yb 3+ absorption (at 978 nm) vs concentration of Yb 3+ ions (not shown), indicating successful incorporation of Yb 3+ into the prepared glasses. A blue shift of the absorption edge is also observed, indicating that the addition of Yb 3+ caused a change in the glass structural units from TeO 4 (tbp=trigonal bi‐pyramid) to TeO 3 (tp=trigonal pyramid) . Similar changes were reported recently for Nd 3+ added to a TW host, promoting a slight reduction in its phonon energy (~942 cm −1 ) …”
Section: Resultssupporting
confidence: 83%
“…The excitation and emission transitions, as well as the cross‐relaxations [between Nd 3+ ions (CR 1 ) and between Nd 3+ and Yb 3+ (CR 2 and CR 3 )] and multiphonon decay, are indicated by solid arrows, dashed arrows, and sinusoidal arrows, respectively. In our recent investigation of Nd 3+ ‐doped tungsten‐tellurite glasses, we observed that the cross‐relaxation rate ( W CR ) associated with the CR 1 energy transfer increased significantly as the Nd 3+ concentration increased . However, in this study, W CR1 is constant due the fixed Nd 3+ concentration in the co‐doped samples.…”
Section: Resultscontrasting
confidence: 62%
See 3 more Smart Citations